Sustainability Dilemmas of our EU-Accession - Szlávik, János (Theory, Methodology, Practice – Review of Business and Management, 2005)
The principle of sustainable development was formulated in the Amsterdam Treaty as a basic principle of the European Union in 1997. The issues of sustainable economic development and social welfare are being formulated as conflicting aims from time to time during the Hungarian accession process to the European Union, as well. We can set a real aim that the economic growth should serve for the aims of sustainability during the accession.